Cinética da degradação térmica de antocianinas de alaybilí (Vaccinium floribundum Kunth) e macha-macha (Gaultheria glomerata (Cav.) Sleumer) - Huarancca-Huarcaya, Erick; Paredes-Quiroz, Luis Ricardo; Paredes-Estrada, Nivia Marisol; Barragán-Condori, Melquiades; Huamaní-Meléndez, Víctor Justiniano [UNESP] (FapUNIFESP (SciELO), 2022)
Fruits are natural sources of antioxidants, especially anthocyanins. However, these compounds are sensitive to certain environmental or processing factors such as temperature, and there are reports in the scientific literature pointing out that temperature has an influence on the degradation of anthocyanins. In this sense, two native fruits from the Apurímac-Peru, known as alabilí (Vaccinium floribundum Kunth) and macha-macha (Gaultheria glomerata (Cav.) Sleumer) were studied as sources of anthocyanins and their degradation by the action of temperature. Anthocyanin extracts with concentrations of 148 and 224 mg L-1 (mg cyanidin 3-glucoside/L) from alaybilí and macha-macha fruits, respectively, were obtained by ethanol extraction and the degradation kinetic was evaluated at temperatures from 30 ºC to 60 ºC, thus noting that the macha-macha extracts showed greater degradation compared to the alaybilí extracts. It was confirmed that the degradation of anthocyanins was best represented by first-order kinetics, with rate constant ranging from 7.07·10-4 to 5.96·10-3 h-1 for alaybilí and from 1.62·10-3 to 1.71·10- 2 h-1 for macha-macha, with activation energies of 60.2 and 70.4 kJ mol-1, respectively. Both fruits turned out to be sources of anthocyanins, and the anthocyanins presented in the alaybilí fruit had greater stability at temperature.
Kinetic of thermal degradation of alaybilí (Vaccinium floribundum Kunth) and macha-macha (Gaultheria glomerata (Cav.) Sleumer) anthocyanins
Keywords: Antioxidants; Bioactive compounds; Ethanol extraction; First order kinetics